NOTCH1 signaling contributes to cell growth, anti-apoptosis and metastasis in salivary adenoid cystic carcinoma - Su, Bo-Hua (Impact Journals LLC, 2014)
Background: Numerous studies have reported both the tumor-suppressive and oncogenic roles of the Notch pathway, indicating that Notch activity regulates tumor biology in a complex, context-dependent manner. The aim of the present study was to identify the role of NOTCH1 in the cell growth and metastasis of SACC. Methods: We analyzed the expression of NOTCH1 in clinical SACC samples using immunohistochemical staining. We silenced the expression of NOTCH1 and overexpressed activated NOTCH1 to elucidate the effects of NOTCH1 on proliferation, migration and invasion. NOTCH1 target genes were validated by real-time PCR. Results: Our results showed that NOTCH1 was upregulated in SACC tissues when compared with normal tissues, and this upregulation was further enhanced in SACC tissues with metastasis and recurrence when compared with SACC tissues without metastasis. Overexpression of NOTCH1 in SACC cells promoted cell growth, migration and invasion, and knockdown of NOTCH1 inhibited cell proliferation in vitro and tumorigenicity in vivo by inducing cell apoptosis. Conclusions:The results of this study suggest that NOTCH1 plays a key role in the cell growth, anti-apoptosis, and metastasis of SACC. NOTCH1 inhibitors might therefore have potential therapeutic applications in treating SACC patients by inhibiting cancer cell growth and metastasis.